Cambios recientes en la sistemática y taxonomía de murciélagos Neotropicales (Mammalia: Chiroptera) - Solari, Sergio; Martínez-Arias, Víctor (THERYA, 2014)
Introduction: Conservation of biodiversity requires an accurate accounting of the entities (taxa) comprising that diversity, the species. In an ideal system, each entity would have a unique and unequivocal name that would integrate information from other disciplines within a universal concept to ease the communication. In spite of being a comparatively well-known group, the number of recognized species of Neotropical bats continues to increase each year, making the organization and management of this knowledge difficult for the non-taxonomist. Here, we review and detail the most recent proposals in regard to the taxonomy of Neotropical bats to make this information more easily accessible to the non-taxonomist. Methods: We used the list of species (and subspecies) recognized in the last edition of â€œMammal Species of the Worldâ€ (2005) as a starting point. From there, we gathered all relevant papers dealing with taxonomy of Neotropical bat species. We delimited the Neotropical region from the lowlands of tropical Mexico to Tierra del Fuego, including the Caribbean. We did not include fossil, extinct or unnamed species. Results: Since 2005, the number of taxonomic changes (Table 1) has resulted in a net increase of 75 species and eigth genera, with a regional diversity of 380 species in 98 genera (Table 2). This richness increase includes newly recognized taxa (split from previously valid genera or species, often listed as junior synonyms) as well as previously unknown species, discovered in the field or at museum collections (Figure 2). Whereas some genera have increased their species richness by almost 100%, the average increase is around two species per genus. Discussion: The use of molecular genetics in systematics research, with an emphasis on recognition of reciprocally monophyletic groups, has contributed the most to the increase in new names now recognized. Although these revisions may appear to the non-taxonomist as a sign of taxonomic instability, we emphasize that the goal of these studies is to facilitate the integration of genetic, morphological, and biogeographic data to improve our knowledge of these species. We anticipate that further advances will continue as we increase exploration and research, together with the use of multiple sources of taxonomic information. All these data should enhance confidence and support for these results, and hopefully a broader agreement among Neotropical bat researchers. Key words: taxonomic update, biodiversity, species, genera, nomenclature.